Everyone is searching for it and those who acquired it enjoy better mental health: a latent profile analysis of Chinese adolescents’ meaning in life - Zhou, Xiaohua; Yu, Lu; Deng, Chen; Ren, Yaoxiang; Du, Meng (Frontiers in Psychology, 2024)
Objective: Associated with increasing percentages of depression and anxiety among youth, one factor is adolescents' lacking meaning in life (MIL). The importance of living a meaningful and purposeful life cannot be overstressed, especially for adolescents who are in a critical life stage and have just experienced a three-year-long global health crisis, i.e., COVID-19. Although prior studies have examined adolescents' MIL, most of them have adopted a variable-centered approach. The present study adopts a person-centered approach to investigate the updated MIL among Chinese adolescents in the aftermath of the COVID-19, the related demographic factors to the profile classification, and the differences in mental health among adolescents in different MIL classes. Method: A questionnaire consisting of MIL, depression, anxiety, stress, as well as demographic information was administered to a total of 1196 Chinese adolescents (mean age = 13.07 ± 0.58, 44.73% are female). A three-step latent profile analysis was conducted. Results and Discussion: This study revealed that (1) adolescents can be categorized into three classes: High MIL, Medium MIL, and Low and Searching MIL. (2) Adolescents who came from intact families and whose mothers had higher education levels were more likely to be classified in the High MIL class rather than in the Low MIL class. And (3) Adolescents with high MIL enjoyed the best mental health, those with the medium MIL experienced moderate mental health, and those with low MIL and were still searching for MIL showed the poorest mental health. External support may be needed in the search process to Chinese adolescents. Future research could delve into the process of searching for MIL and identify the challenges that adolescents encounter when forming their sense of MIL.